Kebebasan berekspresi dan paradoks privasi dalam hubungan pertemanan - Saidah, Musfiah; Irwansyah, Irwansyah (Faculty of Communications Science, Dr. Soetomo University, 2019)
The development of information technology is misinterpreted as a place of expression without control. Social media has blurred the boundary between private space and public space. Frequent phenomena such as taking and using photos of friends without permission. This seems to be a paradox between the right to freedom of expression in friendship. This study aims to assess freedom of expression and the limitations of privacy in cyberspace. The researcher will examine several cases of violations of privacy through photos and their impact on victims. This research method uses a qualitative approach. The technique of collecting data uses interviews, literature studies and documentation. The theory used is the theory of computer- mediated communication and using the concept of a privacy violation to help answer problems in this study. Through this research, it is expected to obtain applicative solutions in an effort to resolve privacy issues and limits in friendship.